Integration of Theoretical Systems and Practice for Sustainable Urban Development - Lin Kuan Wen; Shih Chih Ming (International Journal of Architectural Engineering Technology, 2017)
In this study, we extended the practice of six city theoretical systems, namely “sustainable city,” “eco-city,” “low-carbon city,” “smart city,” “resilient city,” and “knowledge city” to obtain a clear understanding of, the sustainable development of contemporary cities. The study was divided into two parts: First, we executed a review of the literature on the six city theoretical systems, and second, we combined the practice of international organizations and cities corresponding to the aforementioned theories. We elucidated the definition of the theoretical systems and their practical application, representative cities, and relationship with sustainable urban development in terms of international organizations and operations. Finally, we conclude that low-carbon city is the only city theoretical system that can develop international legal initiatives and that it represents the importance and urgency of sustainability in the global urban environment. This study suggests that because different city theoretical systems are considered from the perspective of “sustainable cities”. The sustainable development is dynamic and changes with time and must thus be investigated in depth.